Evidence of Short-Term Contrarian Effect in Abu Dhabi Firms (Global Journal of Management and Business Research, 2017)
This paper examines the existence of short-term contrarian profits in the Abu Dhabi securities exchanges (ADX) for the period of January 2005 through May 2015. This paper provides strong evidence of short-term contrarian profits. The results of this paper present statistically and economically significant profits in the Abu Dhabi stock market over all formation periods. The short-term contrarian strategy used in this paper produces significant average returns of 2.34%, per month over past six-month formation period. Therefore, to utilize from this strategy in ADX, an investor has to sell and buy a pastshort-term winner portfolio and short-term loser portfolio, respectively. The short-term contrarian profits in the ADX can be explained by three-factor model.
Keywords: short-term; contrarian profits; abudhabi securities exchange (ADX); three-factor model